Expanded agroecological niches and redistributed risks in northern Peru's Chicama Valley during late-Holocene ENSO climate changes. (December 2022) - Vining, Benjamin R; Hillman, Aubrey; Contreras, Daniel A; Tejedor, Ernesto
South American arid lands present unique constellations of climatic risk to their human inhabitants, due to volatile events that can create markedly different hydroclimate conditions over interannual–centennial scales. However, a main driver of such volatility – the El Niño/Southern Oscillation (ENSO) – occurs with semiregular periodicity. Paleoclimatic and archeological evidence indicate not only that the strength and periodicity of ENSO patterns have changed over the late-Holocene, but their impacts were likely recognized, adapted to, and perhaps capitalized upon by agriculturalists employing adaptive risk strategies. We examine relationships over the last 1.3 kyr between ENSO periodicity, ecological transitions, and archeological settlement in Peru's Chicama Valley through a coupled paleohydroclimate and agroecology model. We reconstruct periods when ENSO-like conditions dominated past hydroclimates and present a quantitative, spatially-explicit analysis of ecological productivity during modern ENSO-positive hydroclimate conditions. We show that archeological settlement patterns are sensitive to these transformations and reflect efforts to capitalize on expanded agroecological niches. Such expanded niches potentially offset the adverse impacts and risks associated with abrupt ENSO climate events. These results suggest archeological communities were aware of ENSO risk and managed productive strategies accordingly, highlighting the importance of a risk calculus that considers the net ecological effects of climate events.